Charlie Gladstone, rentier or entrepreneur? A case study of contemporary 'Aristocratic Enterprise'. (August 2021) - Grant, Graham; Smith, Rob
Context, including social class is an emerging topic of interest in entrepreneurship studies. According to prevailing orthodoxy, to be upper-class is to be anti-enterprise. Aristocrats are defined through their ownership of land and rentier status and portrayed as conservative being focused on stewardship of their estates, rather than engaging with enterprising activities. This case challenges this traditional perception arguing that aristocrats can pursue an entrepreneurial approach to stewardship in contrast with traditional, low-risk, estate management. The focus is upon aristocrat Charlie Gladstone to explore this phenomenon. Charlie is both rentier and serial entrepreneur who engages his entrepreneurial efforts on the economic reinvigoration of his estates and expanding portfolio of entrepreneurial ventures. The case demonstrates that the enriched human, social and economic capital available to the upper-class can be exploited in an entrepreneurial manner.